Hospitals' Legal Responsibilities for Patient Safety in Healthcare Services - T. Riza Zarzani; Farhan , Farhan; Yusuf Sitinjak; Charly Situmorang (PT. Sinergi Legal Publisher, 2025)
The changes in the national health legal landscape through the enactment of Law No. 17 of 2023 concerning Health have important implications for the construction of hospitals' legal responsibility for patient safety. Previously, Article 46 of the Hospital Law provided an explicit basis for hospital liability for losses resulting from the negligence of healthcare workers. Following the revocation of this provision, questions arose regarding the extent to which the principle of corporate responsibility for hospitals could be maintained and the extent to which legal protection for patients was still guaranteed. This study aims to normatively analyze the conception and regulation of hospitals' legal responsibility for patient safety within the framework of Law No. 17 of 2023, while also examining the problems and implications for patient protection. The method used is normative juridical with a statutory and conceptual approach to the legal relationship between hospitals, healthcare workers, and patients. The results of the study indicate that although explicit formulations such as Article 46 have been removed, the principle of hospital responsibility can still be supported by a combination of the right to health norm, the obligations of healthcare facilities, patient safety standards, and the doctrine of corporate responsibility. However, in practice, there are still gray areas in the integration of civil, criminal, and administrative liability, as well as in the relationship between regulations at the statutory level and implementing regulations. This study recommends the reconstruction of regulations that reaffirm the principle of hospital responsibility, strengthen patient safety systems and culture in hospitals, and develop dispute resolution mechanisms that are fast, transparent, and fair for patients, hospitals, and healthcare workers.